If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5c-4-2c+1=8c-2
We simplify the equation to the form, which is simple to understand
5c-4-2c+1=8c-2
We move all terms containing c to the left and all other terms to the right.
+5c-2c-8c=-2+4-1
We simplify left and right side of the equation.
-5c=+1
We divide both sides of the equation by -5 to get c.
c=-0.2
| 10x^2-89x-9=o | | 5x+5.8-1.1x+0.3x-4= | | (t-1)=9+7 | | 6(2y-3)=6 | | 5x+4=-4+3x | | ((1/4)x^2)-((1/8)x)-1/8=0 | | a-4.70=2.35 | | 4(3+2a)=12-7a | | -x-7=y | | -4/5(n+2)=2/3(n+2) | | 3(v-1)-7=-2(-8v+6)-5v | | 5(p+6)-7(3+p)=5 | | .4c=6 | | 2b-3-4b-7= | | ((1/4)x^2)-((1/8)x)-(1/8)=0 | | -5+9m=-41 | | 2(11+3n)=11+3n | | 8/6=x/27 | | abs(2x)=x^2-8 | | -4(-6x-10)=-104 | | 6/n+5/n=1/2 | | -20-8=-12x+24 | | 9y+(-6x)-5x+1-2y+7= | | 6xn=21 | | -4v=-48 | | 7u+24=5(u+6) | | 81+Z=9z+-7 | | -4(p-5)=6+3p | | x+4-10=20 | | x^2+y^2+12x+14y+69=0 | | 5(2-p)-8p=-34 | | 14-(x+5)=3 |